Synthesis of Highly Functionalized 1,3-Oxathioles via an Unusual [4+1] Annulation of α,α'-Dioxothione with 1,2-Diaza-1,3-dienes - Attanasi, Orazio A.; Favi, Gianfranco; Mantellini, Fabio; Menichetti, Stefano; Moscatelli, Giada; Viglianisi, Caterina (Synlett, 2012)
The present method provides highly functionalized 1,3-oxathioles through an unusual base-promoted [4+1] annulation between α,α'-dioxothione, generated in situ from a phthalimide precursor, and 1,2-diaza-1,3-dienes. An intriguing scaffold comprised of spiro-fused oxathiole and pyrazolone components was also obtained in moderate yield.
Keywords: oxathioles; Michael addition; [4+1] annulation; spiro compounds